Peningkatan Keterampilan Dokkai (Pemahaman Bacaan) Menggunakan Metode Seidoku dan Tadoku Berbasis Capaian Pembelajaran - Rina Yuniastuti (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
This study discusses using seidoku and tadoku methods in learning dokkai (reading comprehension) skills based on learning outcomes. This study was conducted by applying the action research method to improve reading comprehension competence. The research subjects focused on fourth-semester students of the Japanese Literature Study Program who took Shokyuu Dokkai (Basic Reading Comprehension) course. In its implementation, this research was conducted in two cycles of activities which included four stages, namely planning, action implementation, observation, and reflection. In the planning stage, the lecturer in charge of the course determines the learning outcomes of the course which are adjusted to the learning outcomes of the study program. Furthermore, at the implementation stage, learning activities are carried out in accordance with the Semester Learning Plan (RPS) that has been prepared. At this stage, the seidoku method is applied for structured learning activities, and the tadoku method for independent learning activities. At the observation stage, students' understanding of competence is observed and then analyzed. Finally, at the reflection stage, an evaluation of the shortcomings and strengths of the applied method is carried out to be able to design the next improvement step. Based on the formula for calculating the average (mean) of summative scores in two cycles and based on the evaluation of Shokyuu Dokkai learning activities, the use of seidoku and tadoku methods are effective in improving students' reading competence and comprehension.